2022
DOI: 10.1515/med-2022-0579
|View full text |Cite
|
Sign up to set email alerts
|

Xylooligosaccharides and aerobic training regulate metabolism and behavior in rats with streptozotocin-induced type 1 diabetes

Abstract: Type 1 diabetes mellitus is characterized with decreased microbial diversity. Gut microbiota is essential for the normal physiological functioning of many organs, especially the brain. Prebiotics are selectively fermentable oligosaccharides [xylooligosaccharides (XOS), galactooligosaccharides, etc.] that promote the growth and activity of gut microbes and influence the gut–brain axis. Aerobic exercise is a non-pharmacological approach for the control of diabetes and could improve cognitive functions. The poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…25 Choneva et al (2022) also found that XOS reduced the malondialdehyde levels in STZ-induced T1D rats. 26 These studies support the ameliorative role of XOS in glucose metabolism disorders and/or IR in the situation of prediabetes, T1D and T2D. However, little is known about the role of XOS in glucose metabolism disorders and IR in the situation of GDM.…”
Section: Discussionmentioning
confidence: 56%
“…25 Choneva et al (2022) also found that XOS reduced the malondialdehyde levels in STZ-induced T1D rats. 26 These studies support the ameliorative role of XOS in glucose metabolism disorders and/or IR in the situation of prediabetes, T1D and T2D. However, little is known about the role of XOS in glucose metabolism disorders and IR in the situation of GDM.…”
Section: Discussionmentioning
confidence: 56%